Solution structure of stem-loop α of the hepatitis B virus post-transcriptional regulatory element - Schwalbe, Martin (Oxford University Press, 2008)
Chronic hepatitis B virus (HBV) infections may lead to severe diseases like liver cirrhosis or hepatocellular carcinoma (HCC). The HBV post-transcriptional regulatory element (HPRE) facilitates the nuclear export of unspliced viral mRNAs, contains a splicing regulatory element and resides in the 3′-region of all viral transcripts. The HPRE consists of three sub-elements α (nucleotides 1151–1346), β1 (nucleotides 1347–1457) and β2 (nucleotides 1458–1582), which confer together full export competence. Here, we present the NMR solution structure (pdb 2JYM) of the stem-loop α (SLα, nucleotides 1292–1321) located in the sub-element α. The SLα contains a CAGGC pentaloop highly conserved in hepatoviruses, which essentially adopts a CUNG-like tetraloop conformation. Furthermore, the SLα harbours a single bulged G residue flanked by A-helical regions. The structure is highly suggestive of serving two functions in the context of export of unspliced viral RNA: binding sterile alpha motif (SAM-) domain containing proteins and/or preventing the utilization of a 3′-splice site contained within SLα.